2007
DOI: 10.1371/journal.pone.0000962
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Analysis of Chemical and Temporal Patterns of Cuticular Hydrocarbons in Male Drosophila melanogaster

Abstract: Drosophila Cuticular Hydrocarbons (CH) influence courtship behaviour, mating, aggregation, oviposition, and resistance to desiccation. We measured levels of 24 different CH compounds of individual male D. melanogaster hourly under a variety of environmental (LD/DD) conditions. Using a model-based analysis of CH variation, we developed an improved normalization method for CH data, and show that CH compounds have reproducible cyclic within-day temporal patterns of expression which differ between LD and DD condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 44 publications
1
32
1
Order By: Relevance
“…The aliphatic dienes heptacosadiene (C 27 H 52 ) and nonacosadiene (C 29 H 56 ) are the most prominent components found in female profiles. Previous GC/MS studies also identified these compounds as being the most abundant in females[19, 21]. Heptacosene (C 27 H 54 ) and nonacosene (C 29 H 58 ), two other well-characterized female CHs, could not be unambiguously identified due to overlapping signals from other CHs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aliphatic dienes heptacosadiene (C 27 H 52 ) and nonacosadiene (C 29 H 56 ) are the most prominent components found in female profiles. Previous GC/MS studies also identified these compounds as being the most abundant in females[19, 21]. Heptacosene (C 27 H 54 ) and nonacosene (C 29 H 58 ), two other well-characterized female CHs, could not be unambiguously identified due to overlapping signals from other CHs.…”
Section: Resultsmentioning
confidence: 99%
“…Perfuming of courtship targets was performed using a method described by Kent et al [21]. Briefly, 6 – 8 live female flies were placed in a vial coated with lyophilized HPTLC-extracted CH503 or blank fractions (see above) and gently vortexed for 3 × 20 sec with a 20 sec pause between each bout.…”
Section: Methodsmentioning
confidence: 99%
“…Th e turnover of cuticular compounds has been studied in very few insects, mostly in solitary insects and in particular during the modifi cation during the sexual maturity cycle. Kent et al (2007) studied the diurnal cycles of Drosophila melanogaster males. Certain compounds seemed to have a greater variability.…”
Section: Discussionmentioning
confidence: 99%
“…Each individual produces a blend of CHCs and the characteristics of this blend can vary genetically as well as with age, sex, diet and geographic origin within a species (Ferveur, 2005). Some blends show diurnal rhythms (Kent et al, 2007). Analyses of divergence in CHC blend among species suggest a role of CHCs in species recognition and speciation in Drosophila (for example, in Drosophila mojavensis group; Etges and Jackson, 2001).…”
Section: Chemosensory Traits In Speciationmentioning
confidence: 99%